Overeducation, skill mismatches, and labor market outcomes for college graduates - Peter J. Sloane; Kostas Mavromaras (IZA World of Labor, 2020)
Evidence shows that many college graduates are employed in jobs for which a degree is not required (overeducation), and in which the skills they learned in college are not being fully utilized (overskilling). Policymakers should be particularly concerned about widespread overskilling, which is likely to be harmful to both the welfare of employees and the interests of employers as both overeducation and overskilling can lead to frustration, lower wages, and higher quitting rates while also being a waste of government money spent on education.
Keywords: I20; J24; 330; overeducation; skill mismatch; overskilling; graduates